Neural processing of criticism and positive comments from relatives in individuals with schizotypal personality traits. (February 2013) - Premkumar, Preethi; Williams, Steven CR; Lythgoe, David; Andrew, Christopher; Kuipers, Elizabeth; Kumari, Veena
Abstract Objectives. High negative expressed emotion by family members towards schizophrenia patients increases the risk of subsequent relapse. The study aimed to determine whether individuals with high schizotypy (HS) and low schizotypy (LS) would differ in activation of brain areas involved in cognitive control when listening to relative criticism. Methods. Twelve HS and 12 LS individuals listened to relative's critical, positive and neutral comments about them while undergoing functional MRI. Activation maps in the two groups during the comments were compared using SPM5. Results. The left superior frontal and middle frontal gyri and bilateral posterior cingulate cortex were activated during criticism, compared to neutral comments, across all participants. While there were no group differences in brain activity for criticism versus neutral comments, the HS group, who had lower current mood relative to the LS group, activated to a lesser extent the thalamus, insula, putamen and brain stem during positive, compared to neutral, comments. Conclusions. Listening to relative criticism in healthy individuals engages brain areas for cognitive control of negative emotion and self-referential processing. However, HS individuals may have an attenuated ability to respond to rewarding aspects of positive comments due to their lower current mood.